On the effectiveness and efficiency of discrete-event simulation for designing manufacturing systems - Potter, J. (Cranfield University, 2000)
This thesis investigates the effectiveness (doing the right thing) and efficiency (doing the thing right) of computer-based discrete-event simulation for designing manufacturing systems. This investigation looked at the use of this technology in the manufacture of discrete components in aerospace, automotive and consumer electrical (white goods) industries and for material handling (warehousing). Continuous and quasi-continuous manufacture have not been investigated and hence, the conclusions of this thesis cannot be generalised to cover these areas. Working hypotheses were developed and tested which looked at how discrete-event simulation influences the understanding of, confidence in and credibility of a system's design. Testing these working hypotheses lead to conclusions about how discrete-event simulation affects the quality of decision making and the lead-time to develop, commission and ramp-up a manufacturing facility. The following five factors were identified as influencing the efficiency of delivery of discrete-event simulation: l. Management of the simulation study and its intended benefits. 2. Management of customers' expectations. 3. Use of geometric animation. 4. Validation and establishing credibility. 5. How simulation's effectiveness varies over the life of a manufacturing system development project. A qualitative research methodology was employed to test these working hypotheses and to explore these efficiency factors. Twenty-three research subjects, in twelve companies, were drawn from the following three groups: ° Modellers (who provide the modelling service). ° Team members (who are closely involved with supporting the execution of a simulation study). Senior decision makers (who are not closely involved with the execution of the study, but who review its findings). A good practice model was developed for the efficient acquisition and application of the technology. This model consists of the following six elements: 1. Establishing and maintaining a DES modelling capability in the organisation. 2. Knowing whether to use DES modelling for this manufacturing system and when. 3. Defining the study's objectives and their means of measurement. 4. Specify responsibilities for supporting the study and implementing its findings. 5. There is no improvement in the effectiveness of DES modelling in using 2D rather than 3D geometric animation. 6. 3D geometric animation can increase the efficiency of a study, if used appropriately. Conclusions were made about the effectiveness of discrete-event simulation, how the above mentioned factors influence its efficiency of delivery and how to implement the good practice model.